2002
DOI: 10.21775/cimb.004.111
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomics: Genome-Wide Study of Methylation Phenomena

Abstract: Epigenetics is one of the key areas of future research that can elucidate how genomes work. It combines genetics and the environment to address complex biological systems such as the plasticity of our genome. While all nucleated human cells carry the same genome, they express different genes at different times. Much of this is governed by epigenetic changes resulting in differential methylation of our genomeor different epigenomes. Individual studies over the past decades have already established the involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(2 citation statements)
references
References 168 publications
(170 reference statements)
0
2
0
Order By: Relevance
“…This approach is invaluable in observing the differential expression of genes providing important insights for further research [5 and 6]. Epigenetics are the heritable changes that occur beyond alterations in the DNA sequences, which include DNA methylation and post translational modification of chromosomal proteins [7,8]. The combination of epigenetics and genomics has given rise to novel omics technique known as epigenomics, which aims to unravel the genetic regulation and its role in plant breeding unlike genomics, epigenomics is also influenced by biotic and abiotic stress.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is invaluable in observing the differential expression of genes providing important insights for further research [5 and 6]. Epigenetics are the heritable changes that occur beyond alterations in the DNA sequences, which include DNA methylation and post translational modification of chromosomal proteins [7,8]. The combination of epigenetics and genomics has given rise to novel omics technique known as epigenomics, which aims to unravel the genetic regulation and its role in plant breeding unlike genomics, epigenomics is also influenced by biotic and abiotic stress.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence suggests that one mechanism for gene by environment interactions that differentiates risk versus resilience involves epigenetic processes (Yehuda & Bierer, 2009 ; Yehuda & LeDoux, 2007 ). The most studied epigenetic mark in the field of mental health is DNA methylation (DNAm), a chemical modification of DNA at cytosine-guanine dinucleotides (CpGs) which can alter gene regulation (Novik et al, 2002 ). It has been suggested that the epigenome can accommodate environmental influences in the form of long-lasting DNAm modifications which alter the central nervous system’s structures and functioning (Aristizabal et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%